THE HISTORY OF CERAMIC DECORATIONS APPLIED TO CULTURAL HERITAGE OBJECTS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Architectural ceramic-tiling refers to the art of ceramics, or pottery, which is a world unto itself. In particular, it starts with the basic processing and decoration of clay in ancient times, and in the centuries that followed, it is baked in a fire oven. This clay is then used to make raw bricks, which are used to make tiles, which are used to decorate our magnificent architectural monuments. The evolution of bricklaying as an art form has been the subject of several studies. A vast vocabulary of words and concepts has organically grown in the talks and hands-on experiences of folk artisans due to extensive research and years of work in ceramics and tiling.